2021
DOI: 10.1136/bmjgast-2020-000544
|View full text |Cite
|
Sign up to set email alerts
|

Do gastroenterologists have medical inertia towards coeliac disease? A UK multicentre secondary care study

Abstract: ObjectiveThis study aimed to assess if there is secondary care medical inertia towards coeliac disease (CD).DesignGroup (1): Time from primary care presentation to diagnostic endoscopy was quantified in 151 adult patients with a positive endomysial antibody test and compared with 92 adult patients with histologically proven inflammatory bowel disease (IBD). Group (2): Across four hospitals, duodenal biopsy reports for suspected CD were reviewed (n=1423). Group (3): Clinical complexity was compared between know… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…20 Nevertheless, there seems to be a tendency of inertia towards CD within the medical community. 21 Unlike CD, work loss in inflammatory bowel disease has been extensively studied. 19,22,23 In comparison to the most recent such study, 19 also conducted in Sweden, patients with CD had similar, if not more, work loss than patients with ulcerative colitis (w12 vs w14 days), but less work loss than patients with Crohn's disease (w34 vs w14 days).…”
Section: Interpretation Of Results In Relation To Previous Literaturementioning
confidence: 99%
“…20 Nevertheless, there seems to be a tendency of inertia towards CD within the medical community. 21 Unlike CD, work loss in inflammatory bowel disease has been extensively studied. 19,22,23 In comparison to the most recent such study, 19 also conducted in Sweden, patients with CD had similar, if not more, work loss than patients with ulcerative colitis (w12 vs w14 days), but less work loss than patients with Crohn's disease (w34 vs w14 days).…”
Section: Interpretation Of Results In Relation To Previous Literaturementioning
confidence: 99%
“…We suggest that diagnostic delays in adults can be associated with a non-specific varied clinical picture, but also with this diagnostic approach based on histopathological assessment. A recent study performed in the United Kingdom revealed that the majority of endoscopists did not follow guidelines for diagnostic endoscopy for CD, which led to a reduction in diagnosis rates by over 50% [ 17 ]. In addition, the longer diagnostic delay observed in adults might result from the fact that, in Poland, CD has been regarded as a pediatric disease until quite recently [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A routine duodenal biopsy in patients performing gastroscopy for refractory GERD or anemia is not a cost-effective approach, so the indication for biopsy should always have the right reasons, including to justify the cost [65,66]. Not least, there is low adherence to the current recommendation of multiple biopsy sampling, with some studies showing that some patients are diagnosed based on a single biopsy specimen [67][68][69].…”
Section: Discussionmentioning
confidence: 99%